Prevalence and risk factors for repeat induced abortion among Chinese women: a systematic review and meta-analysis. (2nd November 2021) - Liu, Jinlin; Duan, Zhuqing; Zhang, Hairui; Wen, Chunmei; Tang, Longmei; Pei, Kaiyan; Zhang, Wei-Hong
Abstract: Objectives: Repeat induced abortion is a significant public health problem in China. International knowledge about repeat induced abortion and its associated risk factors in Chinese women is scarce, and existing studies are hard to access for international scholars because most are published in Chinese. A systematic review was conducted to analyse the prevalence of repeat induced abortion among Chinese women and determine correlated risk factors. Methods: Seven electronic databases were systematically searched. Data on the prevalence of repeat induced abortion and related factors were extracted and pooled using a meta-analysis and narrative approach. Results: Of 2458 articles retrieved from seven databases, 21 were included in the study. The overall pooled prevalence of repeat induced abortion was 43.1% (95% confidence interval 36.7%, 49.5%). Of 25 exposures extracted, 15 factors were significantly correlated with repeat induced abortion, comprising seven individual demographic factors (i.e., age, education, employment, migrant status, parity, unhealthy lifestyle habits and region of residence), four reproductive health- and contraception-related factors (i.e., age at sexual debut, history of sexual activity, contraceptive knowledge and having a regular sexual life) and four sexual partner-related factors (i.e., multiple sexual partners, age of sexual partner, educational level of sexual partner and cohabitation with sexual partner). Conclusion: The study findings highlight the problem of repeat induced abortion in China and suggest the need for government and civil society to increase efforts to reduce the alarming risks of repeat induced abortion in Chinese women and make them and their sexual partners more aware and protective of their sexual and reproductive health.